Estudio de factibilidad para el desarrollo de un sistema de información para el Hotel "Naranja Sweet" del cantón Las Naves - García Viteri, Damián Isaías (2020)
There are countless departments and systems, managing a hotel today can be a very complex challenge. To remain competitive in the hotel industry today, it is essential to use software applications for the growth of a hotel, where these are easily and smoothly integrated with other programs; Hoteliers will not only benefit from significant cost savings but also increase the productivity of their company. Such cases in the Orange Sweet Hotel that is located in the Canton Las Naves-Province of Bolívar diverse and tourist area, The Processes that are carried out are manually, that is, they are carried out in registration sheets evidencing that the activities are not carried out in an optimal or safe way. This does not allow the Administrator to access information instantly and in real time as what is a technological tool. In this case study qualitative research was applied, which is based on the inductive methodology where techniques are used to collect data such as unstructured observation, open interviews, document review, evaluation of personal experiences and based on an interpretative perspective, centered on the understanding of the meaning of the actions carried out by living beings, the hypotheses are developed during the research process and is based on the methods of data collection not standardized to numerical measurement, its purpose is to reconstruct reality as As if examining the actors of a previously defined social system, the important characteristics that apply to the qualitative approach are: it shows collection and analysis in which they are elaborated in a synchronized way.